Potensi Pengembangan Usaha Peternakan Sapi Babussalam Al Barokah Pada Kawasan Sapi Ternak Di Kabupaten Bogor - Puti Lenggo Ginny; Canggih Gumanky Farunik; Tjong Se Fung (eCo-Buss, 2021)
Dairy Farming Business experienced an increase in production as of 2017, but was only able to meet 22% of the national milk consumption needs in the same year. This is in the perspective of a business feasibility study, it is considered that it has not maximized its potential. The main reason why the national milk demand is high is the high dependence of dairy farmers on the milk processing industry. On the other hand, the milk processing industry itself prioritizes imported raw materials. This situation will not be profitable for cattle farmers, where they are like "trapped" in the supply chain without any certainty to develop their business. This study aims to answer these problems through a business feasibility study approach, so that it can provide recommendations for dairy farmers and entrepreneurs to develop their businesses, according to their potential. The approach used in this research is a business feasibility study analysis by taking into account the non-financial and financial aspects simultaneously to find the potential for development in a business. Non-financial aspects consist of law, market and marketing, technical and technology, management and human resources, economic and social, environment. While the financial aspect consists of financial payback period, net present value, internal rate of return, profitability index. The expected results of this research are the feasibility of livestock business and business development recommendations based on their potential.